Methodology of Teaching Folk Handicrafts and National Costume Motifs in Visual Arts Lessons - Usmonova Ruxshona Feruz qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the methodology of teaching schoolchildren folk handicrafts and national costume motifs in visual arts lessons. The study examines effective pedagogical approaches for developing students’ artistic skills, aesthetic taste, and creative thinking while familiarizing them with cultural heritage and national identity. The article provides practical recommendations for lesson planning, preparation, and implementation through individual and group activities aimed at enhancing students’ artistic expression and creative engagement.